Multimodal, transmedial, and trans-European perspectives for online language teaching and learning: II YUFE – Ukraine seminar - Joanna Winska; Iryna Shevchenko (Когниция, коммуникация, дискурс)
This review explores the Second YUFE – Ukraine seminar, held from November 12th to 14th, 2024. Young Universities for the Future of Europe is a European University alliance of 10 higher education institutions. Hosted by the University Centre for Foreign Languages at Nicolaus Copernicus University in Toruń—one of Poland’s largest state universities—and supported by the Polish National Agency for Academic Exchange (NAWA), the seminar marked a significant trans-European collaboration. This event brought together foreign language educators and researchers from Poland, Ukraine, Cyprus, Finland, Georgia, and Belgium, focusing on the theme of online language teaching and learning, which underscored its relevance.